Diet Improvements in Community-Dwelling Older Adults in the Mobility and Vitality Lifestyle Program. (May 2022) - Cheng, Jessica; Burke, Lora E.; Venditti, Elizabeth M.; Sereika, Susan M.; Glynn, Nancy W.; Albert, Steven M.; Newman, Anne B.
This analysis examined whether a community-based intervention produced measurable improvements in dietary habits. MOVE UP combined translational, evidence-based weight management and healthy aging interventions using a non-randomized design. This 13-month intervention included 32 group sessions, explicit calorie and physical activity goals, self-monitoring, and nutrition education. Participants were ( N = 297) older adults (mean = 68.0 years) with overweight and obesity. Diet was measured using Rate Your Plate (RYP)-Heart. Changes in scores from baseline to 5, 9, and 13 months were assessed using mixed models. MOVE UP successfully shifted eating patterns from baseline (mean = 50.9) to 5 months (mean = 55.1) ( p < .0001) adjusted for age, sex, and race. Improvements persisted through 9 (mean = 54.7) and 13 months (mean = 55.0) ( p < .0001). Although participants were not prescribed a specific diet, RYP-Heart indicated positive dietary shifts. Community-implemented behavioral weight loss interventions may assess the modifiability of dietary habits with a simple, easy-to-administer tool.